2010
DOI: 10.1007/s00234-010-0744-z
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging of hydrogel filament embolic devices loaded with superparamagnetic iron oxide or gadolinium

Abstract: Based on these results, we are focusing on loading hydrogel filaments with SPIO in an effort to provide adequate visualisation for use in MR-guided interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…52 Hydrogel filaments containing gadolinium or SPIO were invented to be visualized by MRI and applied to embolization for the treatment of intracranial aneurysm. 53 More precise and accurate mechanical properties such as stiffness and elasticity can be assessed using magnetic resonance elastography (MRE), which uses low-frequency shear wave motion generated by an acoustic actuator coupled to the tissue of interest. The acquired shear wave images can be utilized to assess the mechanical property called the shear elastic modulus, presenting the proportionality relationship between lateral stress and strain in a material.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…52 Hydrogel filaments containing gadolinium or SPIO were invented to be visualized by MRI and applied to embolization for the treatment of intracranial aneurysm. 53 More precise and accurate mechanical properties such as stiffness and elasticity can be assessed using magnetic resonance elastography (MRE), which uses low-frequency shear wave motion generated by an acoustic actuator coupled to the tissue of interest. The acquired shear wave images can be utilized to assess the mechanical property called the shear elastic modulus, presenting the proportionality relationship between lateral stress and strain in a material.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Current embolic materials are either inherent radiopaque or containing an imaging agent. 6 For example, copolymers of acrylate and co-monomers containing iodine are commonly used for embolic materials. [7][8][9][10] However, the preparation of such copolymers is complicated and monomers containing iodine are potentially toxic.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is commonly used for the in vivo visualization of hydrogels and evaluation of their degradation over time. [31][32][33][34] The experimental design of this study is shown in Figure 2, panel a. For the injections, the PF-A + AuNPs and PF-A samples were pre-cross-linked using CaCO 3 and D-(+)-gluconic acid 𝛿-lactone (GDL).…”
Section: In Vivo Degradation Of Hydrogelsmentioning
confidence: 99%